Optimization of Telkomsel 4G LTE Network in Taman Panorama Baru Area - Afrizal Yuhanef; Deri Latika Herda; Herry Setiawan; Dhea Veriska (Brilliance: Research of Artificial Intelligence, 2026)
The Bukittinggi City New Panorama Tourism Park is one of the most visited destinations, requiring optimal cellular network quality to support communication and data services. This study aims to analyze the performance of Telkomsel’s 4G LTE network in the area, plan necessary improvements, and optimize network performance using Atoll software. The initial data were collected through a drive test by measuring key parameters such as Reference Signal Received Power (RSRP), Signal to Interference plus Noise Ratio (SINR), and throughput. Field measurements revealed that several areas still exhibited RSRP values ? -110 dBm, low SINR, and existing bad spots, indicating that the service quality had not yet reached optimal performance. Network optimization was carried out by adjusting antenna parameters including azimuth, tilt, and transmit power using the Automatic Cell Planning (ACP) method. The simulation results in Atoll after optimization showed improved RSRP coverage, a significant increase in SINR, and higher predicted throughput compared to the initial condition. However, discrepancies were found between simulation and field results, particularly in throughput, due to propagation model limitations, physical obstructions, and environmental variations. In conclusion, the implemented optimization successfully enhanced the overall network performance, although further evaluation is required to better align the simulation outcomes with real field conditions.